Tests and proofs : 10th International Conference, TAP 2016, held as a part of STAF 2016, Vienna, Austria, July 5-7, 2016. Proceedings /: 10th International Conference, TAP 2016, held as a part of STAF 2016, Vienna, Austria, July 5-7, 2016. Proceedings. (2016) - Unknown
No abstract available